Pengaruh Pendapatan Asli Daerah, Pendapatan Perkapita, dan Tingkat Pendidikan Terhadap Tingkat Kemiskinan di Provinsi Bali Tahun 2006 - 2011 - Iswara, I Made Anom; Indrajaya, I Gusti Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2014)
The purpose of this study was to determine the effect of regional income, per capita income, and level of education on the level of poverty in the province of Bali in 2006-2011. This study used a quantitative research by looking at reports revenue, earnings per capita, the level of public education and the amount of poverty in the province of Bali. This research was conducted in the province of Bali. The data analysis technique used in this study is multiple linear regression.  It was found that the level of education has a negative and significant impact on poverty levels. The results further showed that revenue and income per capita in partial no effect on the level of poverty. And then, local revenues, per capita income, and education level simultaneously significant effect on the level of poverty.
Keywords: Pendapatan Asli Daerah; Pendapatan Perkapita; Tingkat Pendidikan; Tingkat Kemiskinan